Pre-operative diagnosis of ovarian ectopic pregnancy: a challenge to practicing clinician - Valecha, Shalini Mahana; Bashani, Dolly; Gedam, Jaya; ., Pandeeswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The first case of primary ovarian ectopic pregnancy was reported by St. Maurice in 1689. Primary ovarian ectopic pregnancy is rare entity, with incidence of around 3% of all ectopic pregnancies. The aim of present case report is to study the role of different modalities like clinical findings, biochemistry, sonography, surgery and histopathology in diagnosis of primary ovarian ectopic pregnancy. Authors present a case of a 24 years old female with history of 2 months amenorrhoea, per vaginal spotting and mild intermittent abdominal pain in RIF. Examination was unremarkable and serum βHCG was 2007.5IU/ml. An ultrasound scan showed an ectopic mass in the right adnexa suggestive of a tubal ectopic pregnancy and she underwent surgical management at our institute. At laparoscopy, both fallopian tubes were noted to be normal with an ectopic mass attached to the right ovary with a pedicle. With these unusual laparoscopic findings, possibilities of tubal miscarriage, ovarian pregnancy, or abdominal pregnancy were suspected. Ectopic mass was coagulated and cut through the pedicle with bipolar cautery and specimen was sent for HPE. Our patient made an uneventful recovery and no further medical management was indicated. The diagnosis of right ovarian ectopic pregnancy was finally confirmed by histopathological evidence of the presence of chorionic villi in a background of ovarian stromal tissue, in consideration with Spigelberg’s criteria. Present case highlights the importance of considering non-tubal ectopic pregnancies when making a diagnosis based on ultrasound scan. Pre-operative diagnosis of ovarian ectopic pregnancy still remains a challenge in spite of current medical advances. Despite the benefits and reliability of ultrasound scanning, there will still be situations where the definitive diagnosis can only be made at surgery. However, histopathological examination is confirmatory and always mandatory.